2019
DOI: 10.1016/j.bone.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis, EPO, macrophages, and bone

Abstract: The regulation of erythropoiesis in the bone marrow microenvironment is a carefully orchestrated process that is dependent upon both systemic and local cues. Systemic erythropoietin (EPO) production by renal interstitial cells plays a critical role in maintaining erythropoietic homeostasis. In addition, there is increasing clinical and preclinical data linking changes in EPO and erythropoiesis to altered skeletal homeostasis, suggesting a functional relationship between the regulation of erythropoiesis and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 89 publications
0
54
0
Order By: Relevance
“…Erythropoiesis happens in human red bone marrow after kidneys responses to low levels of oxygen by releasing erythropoietin [35]. Erythropoiesis is a multi-step cellular course by which a primitive multipotent HSC experiences a series of differentiations resulting in production of erythroid lineage, undergoing erythroid progenitors (colony-forming unit erythroid [CFU-E] and burst-forming unit erythroid [BFU-E]), normoblasts, proerythroblasts, early basophilic erythroblasts, late basophilic erythroblasts, polychromatic erythroblasts, orthochromatic erythroblasts, reticulocytes, ultimately differentiating to mature erythrocytes [5,6]. Megakaryopoiesis occurs through a hierarchical series of progenitor cells, multipotent progenitor (MPP), common myeloid progenitor (CMP) and megakaryocyte-erythroid progenitor (MEP), megakaryocyte progenitor (MKP), ultimately differentiating to mature megakaryocytes [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoiesis happens in human red bone marrow after kidneys responses to low levels of oxygen by releasing erythropoietin [35]. Erythropoiesis is a multi-step cellular course by which a primitive multipotent HSC experiences a series of differentiations resulting in production of erythroid lineage, undergoing erythroid progenitors (colony-forming unit erythroid [CFU-E] and burst-forming unit erythroid [BFU-E]), normoblasts, proerythroblasts, early basophilic erythroblasts, late basophilic erythroblasts, polychromatic erythroblasts, orthochromatic erythroblasts, reticulocytes, ultimately differentiating to mature erythrocytes [5,6]. Megakaryopoiesis occurs through a hierarchical series of progenitor cells, multipotent progenitor (MPP), common myeloid progenitor (CMP) and megakaryocyte-erythroid progenitor (MEP), megakaryocyte progenitor (MKP), ultimately differentiating to mature megakaryocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoiesis and megakaryopoiesis are important parts of hematopoiesis [3,4]. Normal erythropoiesis produces about 10 11 new red blood cells (RBCs) every day in an adult human through the commitment of hematopoietic stem cells into erythroid progenitors, which subsequently differentiate into mature RBCs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest for skeletal tissue engineering, the pleiotropic capabilities of EPO include osteogenic and angiogenic potencies. (6)(7)(8)(9)(10) The studies coupling the EPO to bone healing reported that the use of EPO was supraphysiologic dosage and had potential harmful implication like high blood viscosity and consecutive thromboembolic events. Many researches shifted to the use of topical administration of EPO into the bone defect to improve the efficiency of EPO on the bone formation with minimal systemic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The hormone Erythropoietin (EPO) has been used for treating anemia and its angiogenic effects are proven by several researches (8) . It regulates red blood cells generation in the bone marrow together with bone homeostasis (9) . EPO was proved to increase the expression of vascular endothelial growth factors (VEGFs) and bone morphogenetic protein (BMP 2) both play an essential role in vascular formation and the angiogenesis process ((10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…(4) It has been speculated that regulation of erythropoiesis and bone remodeling is coordinated in the hematopoietic stem cell niche. (5,6) This view is supported by both clinical and experimental observations as osteoporosis and fractures are more commonly observed in patients with anemia and polycythemia. Patients with thalassemia (7) or sickle cell disease (8) have low bone mass and increased risk of fractures, and the concomitant anemia is associated with high serum levels of EPO.…”
Section: Introductionmentioning
confidence: 88%